CLINICAL PICTURE AND TREATMENT RESULTS IN PATIENTS WITH SECONDARY HYPERPARATHYROIDISM - N. I. Bogomolov; P. P. Pakhol’Chuk; N. B. Prokhorov (Вестник хирургии имени И.И. Грекова)
The secondary hyperparathyroidism was observed in 23 patients using a program hemodialysis. The parathyroidectomy was applied as a medical aid. A relapse was noted in one case. Clinical signs of hyperparathyroidism were completely terminated by 6 months.